The Analysis of Factors Affecting Entrepreneurial Supply Chain Management in Indonesia - Suranto, Suranto; Narimo, Sabar; Waskito, Titis; Aji Fitriani, Sofa; Susilo, Agus (ExcelingTech, 2020)
This article investigates the effect of five factors indirectly on entrepreneurial supply chain management supply chain management competence and two other factors SCM strategies and performance of firm in Indonesian companies. The problem is that there are factors that can affect the entrepreneurial supply chain management intentions of companies and education system. Those factors can strengthen or even weaken company’ entrepreneurial supply chain management attitudes. Therefore, to deal with this, what must be done first is to identify what factors that influence entrepreneurial supply chain management intentions. This research aims to determine the effect of self-efficacy, locus of control, and professional commitment to the entrepreneurial supply chain management intentions of Accounting company in indonesia. The research method used was a quantitative method. The sample used in this study was 60 Accounting company with probability sampling techniques. The results of this study indicate that there is a positive influence between self-efficacy, locus of control, and professional commitment on entrepreneurial supply chain management intentions of company.